I’RADH SUAMI DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Fakhriyah Annisa Afroo (Qiyas : Jurnal Hukum Islam dan Peradilan, 2018)
Husband’s i’radh In Islamic And Positive Law Perspective, i’radh is the husband who turns away, husband’s i’radh is the beginning  of the cause  of the emergence of nusyuz. In the positive law of Law No. 1 of 1974  concerning Marriage and compilation of Islamic Law does  not  mention  the  problem  of the  husband’s husband explicitly. However,  according  to the author, a husband can be considered as an iadrad  if inside him contains  the elements  of the husband who violate taklik talak. differences and similarities in the views of husbands in the perspective of Islamic law and positive law, among  others.  In Islamic law, it is explicitly mentioned that i’radh in positive law does not explicitly mention  i’radh or nusyuz husband. In Islamic law and positive law both use the path of peace, but when the peace  that is done  is unsuccessful,  the wife can file a divorce. So that this husband could be the cause  of the wife’s divorce  case against  the husband when  he was already  in the behavior, while when he was still within the boundary he could not be the reason  for the divorce